MTOR genetiniu variantu analize Lietuvos aukšto meistriškumo sportininku grupeje - Žažeckyte, G.; Anikeviciute, G.; Gineviciene, V. (Sporto Mokslas-Sport Science, 2024)
The MTOR gene, which encodes the mechanistic kinase target of rapamycin protein, is an important regulator in the processes of cell growth, proliferation, viability, and aging. The MTOR signaling pathway is involved in numerous cellular and physiological processes and controls the molecular cell response to physical stress and adaptation. Depending on the type of training, the MTOR signaling pathway can be activated or inhibited, leading to glucose uptake, lipid and protein biosynthesis, and skeletal muscle growth. All these aspects indicate that MTOR may have a direct influence on human physical performance and suitability for specific sports disciplines. For this reason, sports scientists have begun to investigate the impact of MTOR genetic variants on the physical performance of high-level athletes. During this case-control association study, the significance of two MTOR genetic variants (promoter rs2295080 (T/G) and intron rs11121704 (T/C)) on the physical performance of Lithuanian elite athletes was investigated for the first time. The research involved 243 Lithuanian athletes of high skill, who were divided into three groups based on sports disciplines (endurance, N = 60; speed and strength, N = 91, and team sports, N = 92), as well as 245 sedentary, non-athletic individuals representing the control group. Genomic DNA was isolated from peripheral blood leukocytes. Genotyping was performed by real-time polymerase chain reaction (RL-PCR) using TaqMan technology. The results of the study showed that the frequencies of MTOR rs11121704 (T/C) polymorphism genotypes and alleles did not differ significantly in the study groups (p > 0.05). However, analysis of the MTOR rs2295080 (T/G) marker revealed that the T allele and TT genotype were significantly more common in the endurance athlete group (T/G: 78.3/21.7%; TT/TG/GG: 60.0/36.7/3.3%) compared to the control group (T/G: 66.3/33.7%, p = 0.016; TT/TG/GG: 44.0/44.4/11.5%, p = 0.038). It was found that MTOR rs2295080 TG and GG genotypes decrease the likelihood of becoming a professional athlete (OR = 0.525; 95% CI: 0.295-0.932; p = 0.028). This case-control association study demonstrated that the MTOR rs11121704 (T allele) genetic variant is associated with physical capacity in Lithuanian male athletes, while the rs2295080 variant (T allele and T genotype) leads to better genetic potential in a group of male and female endurance athletes. Thus, an association of MTOR rs2295080 with elite athlete status in endurance sports was established. The results of this study should be further investigated in larger athlete cohorts both in Lithuania and other populations worldwide.